2014
DOI: 10.1002/acr.22152
|View full text |Cite
|
Sign up to set email alerts
|

Atherosclerotic Cardiovascular Disease in Hospitalized Patients With Systemic Sclerosis: Higher Mortality Than Patients With Lupus and Rheumatoid Arthritis

Abstract: Objective. Systemic sclerosis (SSc; scleroderma) patients have an increased risk for atherosclerotic cardiovascular disease (ASCVD), possibly mediated through inflammatory and fibrotic mechanisms affecting the macrovasculature and microvasculature. We utilized the US Nationwide Inpatient Sample to assess the frequency of and mortality risk associated with ASCVD among hospitalized SSc patients. Methods. We examined the frequency and mortality associated with primary diagnoses and procedures related to ASCVD amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 13 publications
0
14
0
3
Order By: Relevance
“…37 El riesgo de muerte durante la hospitalización es más alto en los pacientes con ES y enfermedad cardiovascular aterosclerótica que en los pacientes con esclerodermia sin evidencia de enfermedad cardiovascular y que los pacientes con otras enfermedades inflamatorias sistémicas. 38 El papel del compromiso microvascular y macrovascular en la patogenia de la enfermedad cardiovascular en la ES aún sigue representando un desafío. 39 La compleja interacción entre daño vascular, fibrosis y autoinmunidad convierte a la ES en un modelo interesante para investigar la fisiopatología del daño aterosclerótico en las enfermedades sistémicas autoinmunitarias.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…37 El riesgo de muerte durante la hospitalización es más alto en los pacientes con ES y enfermedad cardiovascular aterosclerótica que en los pacientes con esclerodermia sin evidencia de enfermedad cardiovascular y que los pacientes con otras enfermedades inflamatorias sistémicas. 38 El papel del compromiso microvascular y macrovascular en la patogenia de la enfermedad cardiovascular en la ES aún sigue representando un desafío. 39 La compleja interacción entre daño vascular, fibrosis y autoinmunidad convierte a la ES en un modelo interesante para investigar la fisiopatología del daño aterosclerótico en las enfermedades sistémicas autoinmunitarias.…”
Section: Discussionunclassified
“…37 Patients with SSc with atherosclerotic cardiovascular disease have a higher risk of death during hospitalization in comparison to scleroderma patients without evidence of cardiovascular disease and to patients with other systemic inflammatory diseases. 38 The role of microvascular and macrovascular involvement in the pathogenesis of cardiovascular disease in SSc still remains a challenge. 39 The complex interplay of vascular 40 The investigation of surrogate measures of vascular disease and early vascular aging may help to understand the factors underlying the increased rate of cardiovascular events reported in SSc.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, analysis of a large hospitalization database revealed that 5.4% of 308,452 SSc hospitalizations were related to atherosclerotic CVD (AS-CVD) as the primary discharge diagnosis. Furthermore, this study demonstrated that in-hospital mortality of SSc patients with CVD was significantly higher than SSc patients without CVD, and SLE and RA patients with CVD (21). Although interstitial lung disease (ILD) and pulmonary arterial hypertension (PAH) are the leading causes of death in SSc, it is anticipated that as SSc survival improves with advances in treatment, CVD will further contribute to the mortality burden of SSc.…”
Section: Introductionmentioning
confidence: 91%
“…Interestingly, a recent cross-sectional analysis of a large United States hospitalization database [1993][1994][1995][1996][1997][1998][1999][2000][2001][2002][2003][2004][2005][2006][2007] estimated that approximately 5.4% of 308,452 SSc hospitalizations were associated with atherosclerotic CV disease as a primary discharge diagnosis. The same study also reported that SSc hospitalizations were more likely to result in death than similar hospitalizations of SLE and control patients [16].…”
Section: Discussionmentioning
confidence: 69%